Inexpensive Ruthenium NNS‐Complexes as Efficient Ester Hydrogenation Catalysts with High C=O vs. C=C Selectivities. Issue 6 (31st January 2018) - Stadler, Bernhard M.; Puylaert, Pim; Diekamp, Justus; van Heck, Richard; Fan, Yuting; Spannenberg, Anke; Hinze, Sandra; de Vries, Johannes G.
Abstract: Ru(NNS)(PPh3 )Cl2 (NNS=2‐(methylthio)‐N‐(pyridin‐2‐yl‐methyl)ethan‐1‐amine) was employed in the hydrogenation of α, β‐unsaturated esters, reaching selectivities for the allylic alcohol up to 95% in the hydrogenation of iso‐butylcinnamate. In addition, several ester substrates were hydrogenated with catalyst loadings as low as 0.05 mol%. Surprisingly, selectivity of the hydrogenation of the C=O vs the C=C bonds strongly depends on the solvent. Abstract :